Fungicide use patterns in South African barley production - M. M. Venter; S. I. Hull; C. Bester; P. A. Swanepoel (Journal of Plant Diseases and Protection, 2026)
Fungicide resistance is an escalating threat to barley ( Hordeum vulgare L.) production worldwide. To evaluate use patterns and potential resistance risks, fungicide application data from the South African national barley production traceability and compliance platform, called the Barley Passport (2021–2024) were analysed. Program intensity was consistently high, with three-application regimes dominating and two-application programs declining over time. Single-application programs were rare. Combinations of Succinate Dehydrogenase Inhibitors (SDHI) and Demethylation Inhibitors (DMI) represented the most common spray type (22–25% of fields), while mixtures of DMI, SDHI and Quinone outside Inhibitors (QoI) contributed an additional 15–22%. Together, SDHI-containing programs accounted for approximately 40–45% of all sprays annually. Spatial analysis revealed notable regional variation in fungicide application practices. Certain production regions consistently accounted for the highest number of treated barley fields, while other regions demonstrated a growing shift toward integrated fungicide programmes, particularly those combining SDHI + DMI and QoI chemistries. These patterns suggest differential responses to disease pressure, agronomic conditions, and resistance management awareness across the barley-growing landscape. Barley-on-barley cropping persisted on 20–21% of hectares, reinforcing conditions of elevated disease pressure. These findings show that South African barley production relies heavily on fungicide chemistries with a high risk of resistance development. This underscores the urgent need for integrated disease management and stewardship to preserve fungicide efficacy and ensure the long-term sustainability of the malting barley sector. Given barley’s global importance, insights into regional resistance dynamics and management responses in South Africa offer valuable lessons for international production systems facing similar challenges.

Monitoring of vagrant seals on mid-oceanic islands of the South Atlantic Ocean - M. N. Bester; M. J. Somers (Polar Biology, 2025)
Extra-limital sightings of seals breeding on the Antarctic pack- and fast ice and on sub-Antarctic and temperate islands of the South Atlantic Ocean are summarised. Particular life history events of four vagrant seal species that have turned up on Mid-Atlantic Ridge islands are presented, and the likely arrival of a further three vagrant seal species is speculated upon. The setting up and/or expansion of a recording system underpinned by an appropriate sighting protocol for vagrant seals in which citizen scientists can participate is advanced. Determination of whether range contractions/expansions of seals in the South Atlantic are taking place reflects on the status of the source population(s). Seal vagrancy may conceivably also be involved in the spread of viral diseases such as highly pathogenic avian influenza and rabies. Insights gained through extra-limital sightings of seals may assist with the establishment of conservation strategies.

Extreme herding behavior in adult male sub-Antarctic fur seals - M. N. Bester; G. J. Rossouw (Journal of Ethology, 2025)
We re-analyzed unpublished data on herding behavior in adult male sub-Antarctic fur seals Arctocephalus tropicalis recorded at Gough Island during the 1975/76 austral summer breeding season. The results extend the study of competition and injury in adult males from the same population. Herding behavior is defined and shows that adult males in this population exhibit the most extreme herding behavior of the fur seal genus Arctocephalus. Extreme herding responses result from both human disturbance and in natural settings without human disturbance. Such information is needed for comparative studies about aggression and territorial behavior in otariids.

Territoriality in adult male sub-Antarctic fur seals at Gough Island - M. N. Bester; G. J. Rossouw (Polar Biology, 2025)
We analysed unpublished data on territory size and tenure in adult male sub-Antarctic fur seals Arctocephalus tropicalis recorded at Gough Island, Southern Ocean, during the 1975/76 austral summer breeding season. Adult males ( n =15) remained on their territories for between 35–56 days (mean 45.4±6.7 days). Territory size during the peak breeding season was 21.9 m 2 on average ( n =42), but when partitioned by beach type, average territory sizes were 13.8 ( n =9), 20.1 ( n =17) and 28.3 m 2 ( n =16). Both territory tenure and territory size fall within the reported range of values established in fur seal species which hold territories on land as the predominant male reproductive strategy. We highlight numerous confounding factors that impact comparative studies which should be considered when interpreting theoretical, conceptual, and modelling approaches about territorial behaviour in otariids.

Prevalence of aeroallergen sensitization in a polluted and industrialized area: a pilot study in South Africa’s Vaal Triangle - Dorra Gharbi; Frank Harald Neumann; Jurgens Staats; Marinda McDonald; Jo-hanné Linde; Tshiamo Mmatladi; Keneilwe Podile; Stuart Piketh; Roelof Burger; Rebecca M. Garland; Petra Bester; Pedro Humberto Lebre; et al. (Environmental Monitoring and Assessment, 2025)
This pioneering study evaluates the prevalence of aeroallergens reactivity among atopic populations living in the Vaal Triangle Airshed Priority Area (VTAPA), South Africa. A total of 138 volunteers (51 males and 87 females), of African, colored, white, and Asian ethnicity, and with a mean (range) age of 22 (18–56) years were participating in the study. The study was conducted on the North-West University (NWU) campus in Vanderbijlpark/VTAPA. The International Study of Asthma and Allergies in Childhood questionnaire was utilized for pre-screening to identify individuals with probable allergic dispositions. Subsequently, skin prick testing was conducted using commercial aeroallergen extracts for all confirmed participants with allergy symptoms. One hundred six participants were clinically diagnosed with pollen and fungal spore allergies. The highest allergy prevalence was attributed to Cynodon dactylon ((L.) Pers) (Bermuda grass) (41.5%), followed by Lolium perenne (L.) (ryegrass), grass mix, and Zea mays (L.) (maize) (31.1%), respectively. Moreover, among the tree allergens, Olea (L.) (olive tree) was the most prevalent allergen (20; 18.8%), followed by Platanus (L.) (plane tree) (18; 16.9%). Among the weeds, 16 (15.1%) participants were allergic to the weed mix ( Artemisia ( L. ) (wormwood), Chenopodium (Link) (goosefoot), Salsola (L.) (saltwort), Plantago (L.) (plantain), and 11 (10.3%) to Ambrosia (L.) (ragweed)). Regarding the fungal spores, Alternaria (Fr.) (9; 8.5%) followed by Cladosporium (Link) (5; 4.7%) had the highest skin sensitivity. In this pilot study, our findings provide insights into the prevalence of allergic responses in the study population—underlining the strong impact of allergens of exotic plants—and contribute to the existing aerobiological data in South Africa.

Complementary conservation of South African crop wild relatives for plant improvement - C Bester; NC Le Maitre; M Visser; WC Botes (South African Journal of Botany, 2024)

Exploring the value of ecosystem services at health clinic gardens in a South African context - N. Gwedla; M. Muller; S. S. Cilliers; C. Niesing; P. Bester; M.J. Du Toit (Urban Ecosystems, 2024)
Ecosystem services (ESs) valuation is important for advancing biodiversity objectives and investing in green infrastructure (GI) establishment. Little is known about the potential of health clinic gardens (HCGs) to provide ESs and their potential values. This study sought to determine the plant and bird species composition and potential value of ESs provided by 32 HCGs in two South African district municipalities. HCG sizes range from 513.0m 2 to 13531.0m 2 and each had at least one micro-garden. Among the 312 plant species observed across all HCGs, 60% were exotic. The small HCGs had 31 ± 3.6 different plant species per garden, compared to the medium-sized (32 ± 3.7) and large ones (49 ± 5.2). Provisioning ESs from the observed species were prominent with 17.4 ± 1.16 species potentially used for general well-being, 13.66 ± 1.08 as potential food plants, and 11.91 ± 0.93 potentially raw materials. Trees in HCGs were estimated to sequester up to 163481.87 kg of carbon from trees covering an area of up to 9620.80m 2 . Approximately 1390.70 ± 427.50m 2 of HCG space had the potential to provide a habitat for plants and birds, and 11 bird species were observed across all HCGs. Sixty-three bird nests encountered in 18 HCGs are believed to belong to the Passer domesticus . HCGs resemble other types of gardens like home and domestic gardens, and their rich plant biodiversity positions them as ideal ecosystems to benefit even the most vulnerable members of society. They provide an opportune platform for knowledge upscaling in the cultivation and use of plant species as a supplement of primary healthcare and food security issues in the summer months to the rural, urban, and peri-urban poor in the Global South.

Contest competition and injury in adult male sub-Antarctic fur seals - M. N. Bester; G. J. Rossouw; P. J. van Staden (Journal of Ethology, 2024)
We recorded intra-sexual behaviour of adult male sub-Antarctic fur seals Arctocephalus tropicalis at Gough Island, Southern Ocean, during the 1975/76 summer breeding season. Our re-analysed data address male ‘contest competition’, which relates to the costs of intra-sexual disputes, including fights. We considered the risks/benefits of fighting through investigation of injuries ( n = 353) sustained by adult males ( n = 124) in fights. Injuries were predominantly on the forequarters, especially around the insertion areas of the front flippers (41%) with its sparse pelage, compared to the neck and chest areas combined (29%), an area which is well protected by thick pelage. The infliction of serious, sometimes debilitating, injuries to competitors increases a male’s access to females. Injuries predominate in injured, defeated males that gather at non-breeding sites, suggesting that injuries inflicted by dominant males were successful in excluding competing males from breeding sites.

Aspects of the skin morphology in the sub-Antarctic fur seal Arctocephalus tropicalis - M. N. Bester; M. van Ouwerkerk (Zoomorphology, 2023)
The present study examined whether sweat glands are present in the skin of sub-Antarctic fur seals, Arctocephalus tropicalis , using standard histological procedures and light microscopy. Aspects of the microanatomy and histology of skin were described to elucidate structure and function. Sweat glands were present both in the furred areas of the body trunk, as well as in naked skin areas of the flippers. The density of the apocrine sweat glands appeared higher in fur-covered areas than in naked areas, while the size of sweat glands was similar amongst naked and fur-covered skin. The superficial position of sweat glands in the dermis of naked skin areas and the large, coiled, tubular nature of the secretory portion seem to indicate sweat gland activity in contrast to the deep lying, narrow sweat glands in fur-covered areas.

Integrating Sentinel-2 Derivatives to Map Land Use/Land Cover in an Avocado Agro-Ecological System in Kenya - Eunice W. King’ori; Elfatih M. Abdel-Rahman; Paul Obade; Bester Tawona Mudereri; Marian Adan; Tobias Landmann; Henri E. Z. Tonnang; Thomas Dubois (Remote Sensing in Earth Systems Sciences, 2023)

Cryptorchidism in the sub-Antarctic fur seal Arctocephalus tropicalis - M. N. Bester (Polar Biology, 2023)
The prevalence of cryptorchidism, a condition when one or more testes failed to move to their proper position(s), was evaluated for sub-Antarctic fur seals from Gough Island, South Atlantic. The reproductive tracts of male fur seals ( n = 123) were examined and reproductive organs measured in a previous study. Only one fur seal, a 5-year-old sexually mature male, had one inguinal testis on the right side, and a small abdominal one situated below the kidney on the same side. A matching contralateral testis could not be located, neither in the scrotum or inguinal canal nor within the abdominal cavity. Amongst pinnipeds, cryptorchids rarely occurred in northern fur seals (0.01% to 0.02% prevalence), harbour seals (undetermined prevalence) and in sub-Antarctic fur seals (0.8% prevalence). Inconsequential on a population level, the rare instances of cryptorchidism in seals are interesting curiosities.

Response of Cyclopia subternata to drought stress – assessment of leaf composition, proteomics and product quality - G.S. Mabizela; M. van der Rijst; M.M. Slabbert; P. Mathabe; M. Muller; D. de Beer; M. Stander; J. Colling; B. Walczak; E. Joubert; C. Bester (South African Journal of Botany, 2023)

Towards early response to desert locust swarming in eastern Africa by estimating timing of hatching - Tobias Landmann; Komi M. Agboka; Igor Klein; Elfatih M. Abdel-Rahman; Emily Kimathi; Bester T. Mudereri; Benard Malenge; Mahgoub M. Mohamed; Henri E.Z. Tonnang (Ecological Modelling, 2023)

Bioactive Peptides from African Yam (AVIAIMF and GPADPF) and Taro (NGDF and NGNW) Reveal Multifunctional Antidiabetic Effects Using Biochemical and Cellular Models - Mohammed Auwal Ibrahim; June Cheptoo Serem; Aliyu Dantani Abdullahi; Suleiman Aminu; Abubakar Babando Aliyu; Aliyu Muhammad Musa; Bashir Musa; Megan J. Bester; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2023)

The possibilities of explicit Striga (Striga asiatica) risk monitoring using phenometric, edaphic, and climatic variables, demonstrated for Malawi and Zambia - Emily Kimathi; Bester Tawona Mudereri; Elfatih M. Abdel-Rahman; Saliou Niassy; Henri E. Z. Tonnang; Tobias Landmann (Environmental Monitoring and Assessment, 2022)

Cephalopod diet of juvenile male southern elephant seals Mirounga leonina at Marion Island, South Indian Ocean - M. N. Bester; M. Connan (Polar Biology, 2022)

Dispersion of a southern elephant seal Mirounga leonina to Possession Island, Namibia - M. N. Bester; G. J. G. Hofmeyr; P. A. Bartlett (Polar Biology, 2022)

Application of DNA mini-barcoding reveals illegal trade in endangered shark products in southern Africa - TA Asbury; R Bennett; AS Price; C da Silva; M Bürgener; JD Klein; SN Maduna; N Sidat; S Fernando; AE Bester-van der Merwe (African Journal of Marine Science, 2021)

Estimating maize lethal necrosis (MLN) severity in Kenya using multispectral high-resolution data - Kyalo Richard; Elfatih M. Abdel-Rahman; Sevgan Subramanian; Johnson O. Nyasani; Michael Thiel; Hossein J. Jozani; Christian Borgemeister; Bester T. Mudereri; Tobias Landmann (Applied Geomatics, 2021)

Landscape-scale biogeographic distribution analysis of the whitefly, Bemisia tabaci (Gennadius, 1889) in Kenya - Bester Tawona Mudereri; Emily Kimathi; Tavengwa Chitata; Moleseng Claude Moshobane; Elfatih M. Abdel-Rahman (International Journal of Tropical Insect Science, 2021)

Fish prey of sub-Antarctic fur seals Arctocephalus tropicalis at the Tristan da Cunha Islands, South Atlantic Ocean - M. N. Bester; L. J. Stansfield; T. Glass; P. J. N. de Bruyn (Polar Biology, 2021)

Status of pinnipeds on mid-Atlantic ridge islands, South Atlantic Ocean - M. N. Bester (Polar Biology, 2021)

Complete genome sequence of ornithogalum virus 3 - I. Mostert; R. Bester; D. Aldrich; M. Visser; I. Gazendam; M. Cloete; H. J. Maree; J. T. Burger (Archives of Virology, 2021)

Vagrant sub-Antarctic fur seal at tropical Ascension Island, South Atlantic Ocean - M. N. Bester (Polar Biology, 2021)

New Antidiabetic Targets of α-Glucosidase Inhibitory Peptides, SVPA, SEPA, STYV and STY: Inhibitory Effects on Dipeptidyl Peptidase-IV and Lipid Accumulation in 3T3-L1 Differentiated Adipocytes with Scavenging Activities Against Methylglyoxal and Reactive Oxygen Species - Mohammed Auwal Ibrahim; June C. Serem; Megan J. Bester; Albert W. Neitz; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2020)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

Sub-Antarctic fur seals depredate northern rockhopper penguins at Nightingale Island, Tristan da Cunha - M. N. Bester; B. J. Dilley; D. Davies; T. Glass (Polar Biology, 2020)

Local extinction imminent for southern elephant seals Mirounga leonina at their northernmost breeding site, Gough Island—South Atlantic Ocean - Christopher W. Jones; Michelle M. Risi; Marthán N. Bester (Polar Biology, 2020)

Stalked barnacles on an adult male sub-Antarctic fur seal at Inaccessible Island, Tristan da Cunha - M. N. Bester; P. G. Ryan (Polar Biology, 2019)

Strong genetic isolation despite wide distribution in a commercially exploited coastal shark - Kelvin L. Hull; Tamaryn A. Asbury; Charlene da Silva; Matthew Dicken; Ana Veríssimo; Edward D. Farrell; Stefano Mariani; Carlotta Mazzoldi; Ilaria A. M. Marino; Lorenzo Zane; Simo N. Maduna; Aletta E. Bester-van der Merwe (Hydrobiologia, 2019)

Survival of Planktonic and Sessile Cells of Lactobacillus rhamnosus and Lactobacillus reuteri upon Exposure to Simulated Fasting-State Gastrointestinal Conditions - Kyle B. Klopper; Elanna Bester; Shelly M. Deane; Gideon M. Wolfaardt; Leon M. T. Dicks (Probiotics and Antimicrobial Proteins, 2019)

Early pupping of a sub-Antarctic fur seal at Inaccessible Island, Tristan da Cunha - M. N. Bester; P. G. Ryan (Polar Biology, 2019)

First record of a leucistic sub-Antarctic fur seal - Christopher W. Jones; Michelle M. Risi; Alexis Osborne; Marthán N. Bester (Polar Biology, 2019)

Tuber Storage Proteins as Potential Precursors of Bioactive Peptides: An In Silico Analysis - Mohammed Auwal Ibrahim; Megan J. Bester; Albert W. Neitz; Anabella R. M. Gaspar (International Journal of Peptide Research and Therapeutics, 2019)

Increase of sub-Antarctic fur seals at the Tristan da Cunha Islands - M. N. Bester; M. Wege; T. Glass (Polar Biology, 2019)

Quantitative trait loci (QTL) mapping of blush skin and flowering time in a European pear (Pyrus communis) progeny of ‘Flamingo’ × ‘Abate Fetel’ - Solomon M. Ntladi; Jan P. Human; Cecilia Bester; Jessica Vervalle; Rouvay Roodt-Wilding; Kenneth R. Tobutt (Tree Genetics & Genomes, 2018)

3D implicit modeling of the Sishen Mine: new resolution of the geometry and origin of Fe mineralization - B. Stoch; C. J. Anthonissen; M-J. McCall; I. J. Basson; J. Deacon; E. Cloete; J. Botha; J. Britz; M. Strydom; D. Nel; M. Bester (Mineralium Deposita, 2018)

Flow cytometry: a quick method to determine ploidy levels in honeybush (Cyclopia spp.) - Mlamuli M. Motsa; Cecilia Bester; Margaretha M. Slabbert; Karin Hannweg; Mardé Booyse (Genetic Resources and Crop Evolution, 2018)

Exploring the anti-proliferative activity of Pelargonium sidoides DC with in silico target identification and network pharmacology - A. S. P. Pereira; M. J. Bester; Z. Apostolides (Molecular Diversity, 2017)

Vagrant leopard seal at Tristan da Cunha Island, South Atlantic - M. N. Bester; W. A. Bester; M. Wege; R. A. Schofield; T. A. Glass (Polar Biology, 2017)

First confirmed record of a leucistic Antarctic fur seal pup born outside the Scotia Arc Islands - M. Wege; M. Postma; C. A. Tosh; P. J. N. de Bruyn; M. N. Bester (Polar Biology, 2015)

An alternative method for correcting fluorescence quenching - L. Biermann; C. Guinet; M. Bester; A. Brierley; L. Boehme (Ocean Science, 2015)
Under high light intensity, phytoplankton protect their photosystems from bleaching through non-photochemical quenching processes. The consequence of this is suppression of fluorescence emission, which must be corrected when measuring in situ yield with fluorometers. We present data from the Southern Ocean, collected over five austral summers by 19 southern elephant seals tagged with fluorometers. Conventionally, fluorescence data collected during the day (quenched) were corrected using the limit of the mixed layer, assuming that phytoplankton are uniformly mixed from the surface to this depth. However, distinct deep fluorescence maxima were measured in approximately 30% of the night (unquenched) data. To account for the evidence that chlorophyll is not uniformly mixed in the upper layer, we propose correcting from the limit of the euphotic zone, defined as the depth at which photosynthetically available radiation is ~ 1% of the surface value. Mixed layer depth exceeded euphotic depth over 80% of the time. Under these conditions, quenching was corrected from the depth of the remotely derived euphotic zone Zeu, and compared with fluorescence corrected from the depth of the density-derived mixed layer. Deep fluorescence maxima were evident in only 10% of the day data when correcting from mixed layer depth. This was doubled to 21% when correcting from Zeu, more closely matching the unquenched (night) data. Furthermore, correcting from Zeu served to conserve non-uniform chlorophyll features found between the 1% light level and mixed layer depth.

Vagrant Antarctic fur seals at the Tristan da Cunha Islands - M. N. Bester; P. G. Ryan; W. A. Bester; T. Glass (Polar Biology, 2014)

The diet of the subantarctic fur seal Arctocephalus tropicalis at Marion Island - A. B. Makhado; M. N. Bester; S. Somhlaba; R. J. M. Crawford (Polar Biology, 2013)

Hydrographic influences on the summer dive behaviour of Weddell seals (Leptonychotes weddellii) in Atka Bay, Antarctica - T. McIntyre; L. J. Stansfield; H. Bornemann; J. Plötz; M. N. Bester (Polar Biology, 2013)

Inter-population differences in diving behaviour of adult male southern elephant seals (Mirounga leonina) - B. S. James; T. McIntyre; C. A. Tosh; H. Bornemann; J. Plötz; M. N. Bester (Polar Biology, 2012)

The Marine Mammal Programme at the Prince Edward Islands: 38 years of research - MN Bester; PJN de Bruyn; WC Oosthuizen; CA Tosh; T McIntyre; RR Reisinger; M Postma; DS van der Merwe; M Wege (African Journal of Marine Science, 2011)

Historical isolation and hydrodynamically constrained gene flow in declining populations of the South-African abalone, Haliotis midae - Aletta E. Bester-van der Merwe; Rouvay Roodt-Wilding; Filip A. M. Volckaert; Maria E. D’Amato (Conservation Genetics, 2011)

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - G. J. Greg Hofmeyr; Marthán N. Bester; Steve P. Kirkman; Christian Lydersen; Kit M. Kovacs (Polar Biology, 2010)

A lifetime at depth: vertical distribution of southern elephant seals in the water column - T. McIntyre; P. J. N. de Bruyn; I. J. Ansorge; M. N. Bester; H. Bornemann; J. Plötz; C. A. Tosh (Polar Biology, 2010)

Prey of the Antarctic fur seal Arctocephalus gazella at Marion Island - A. B. Makhado; M. N. Bester; S. P. Kirkman; P. A. Pistorius; J. W. H. Ferguson; N. T. W. Klages (Polar Biology, 2008)

Multiple origins of vagrant Subantarctic fur seals: a long journey to the Brazilian coast detected by molecular markers - Juliana Machado Ferreira; Larissa Rosa de Oliveira; Louise Wynen; Marthán N. Bester; Christophe Guinet; Nadia Moraes-Barros; Felipe Mello Martins; Mônica M. C. Muelbert; Ignacio B. Moreno; Salvatore Siciliano; Paulo Henrique Ott; João Stenghel Morgante (Polar Biology, 2008)

Dispersion during the moult haulout of southern elephant seals at the Courbet Peninsula, Iles Kerguelen - T. H. Setsaas; M. N. Bester; J. H. van Niekerk; J. P. Roux; G. J. G. Hofmeyr (Polar Biology, 2008)

Vagrant Antarctic pinnipeds at Gough Island - J. W. Wilson; M.-H. Burle; M. N. Bester (Polar Biology, 2006)

Elimination of Macrolides, Tiamulin, and Salinomycin During Manure Storage - M. P. Schlüsener; M. A. von Arb; K. Bester (Archives of Environmental Contamination and Toxicology, 2006)

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - G. J. G. Hofmeyr; B. A. Krafft; S. P. Kirkman; M. N. Bester; C. Lydersen; K. M. Kovacs (Polar Biology, 2005)

Do southern elephant seals show density dependence in fecundity? - C. Bradshaw; C. McMahon; M. Hindell; P. Pistorius; M. Bester (Polar Biology, 2002)

Counts of southern elephant seals, Mirounga leonina , at Bouvet Island - S. P. Kirkman; G. J. G. Hofmeyr; M. N. Bester; K. Isaksen (Polar Biology, 2001)

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - S. P. Kirkman; W. Wilson; N. T. W. Klages; M. N. Bester; K. Isaksen (Polar Biology, 2000)

Survivorship of a declining population of southern elephant seals, Mirounga leonina , in relation to age, sex and cohort - P. A. Pistorius; M. N. Bester; S. P. Kirkman (Oecologia, 1999)

Fish prey of fur seals Arctocephalus spp. at subantarctic Marion Island - N. T. W. Klages; M. N. Bester (Marine Biology, 1998)

Changes in population sizes and distribution of fur seals at Marion Island - G. J. G. Hofmeyr; M. N. Bester; F. C. Jonker (Polar Biology, 1997)